Assessment of financial flow in the health system of Serbia in a period 2003-2006 - Gajić-Stevanović Milena; Teodorović Nevenka; Dimitrijević Snežana; Jovanović Dragan (Vojnosanitetski Pregled)
Background/Aim. The main goal of every health policy is not merely the establishment of the health system sustainability, but the accessibility of health services to the whole population, as well. This objective is shared in European Union countries, and the consequence is the implementation of National Health Accounts (NHA). NHA, as a tool for evidence-based management, provides data regarding financial flow in health at national level and alows international comparability. The aim of this study was to determine Serbian overall health spending patterns by National Health Accounts, and to determine health care indices to provide policy makers with internationally comparable health indicators. Methods. A retrospective analysis of healthcare expenditures was obtained from the published final financial reports of relevant state institutions during a period of 2003 to 2006. The various sources of data on healthcare expenditures were connected according to instructions by the OECD 'A System of Health Accounts (SHA)' Version 1.0. Results. The obtained results showed: health expenditures in Serbia made up 8.6%, 8.3%, 8.7% and 9 % of the GDP in 2003, 2004, 2005 and 2006, respectively; the Health Insurance Fund was a predominant financing source of the public sector with 93% in 2006; the largest part of the total health expenditures went towards hospitals and for health services; the expenditure per capita in 2006 was 365 US$; Serbian population finances the state institutions 'out of pocket' with 21.28% of their sources, which was 7.3% of the total healthcare expenditures, and the private institutions with 78.72% of their financial sources, which is 27% of the total healthcare expenditures. In 2006 Serbia allocated financial resources out of GDP in the amount similar to the European Unity, while comparing to the countries of the region, these funds were less only than in Bosnia and Herzegovina. This allocating of financial resources in total, however, was low as the consequence of relatively low level of GDP in Serbia. Conclusion. Establishing NHA provided a pattern of national healtcare spending and allowed a comparison of healthcare system in Serbia with the systems of other countries. Analysing a period 2003- 2006 revealed a similarity between Serbia and the countries of the European Unity in regard to the level of average financial resources allocation for healthcare expressed as a percentage of GDP, as well as in regard to financiers in the system of healthcare. A high purchasing power disparity, however, in healthcare services was observed between the population of Serbia and other European countries.